Diaphragm pacing and independent breathing in individuals with severe Pompe disease - Liberati, Cristina; Byrne, Barry J.; Fuller, David D.; Croft, Chasen; Pitts, Teresa; Ehrbar, Jessica; Leon-Astudillo, Carmen; Smith, Barbara K. (Frontiers in Rehabilitation Sciences, 2023)
Introduction Pompe disease is an inherited disease characterized by a deficit in acid-α-glucosidase (GAA), an enzyme which degrades lysosomal glycogen. The phrenic-diaphragm motor system is affected preferentially, and respiratory failure often occurs despite GAA enzyme replacement therapy. We hypothesized that the continued use of diaphragm pacing (DP) might improve ventilator-dependent subjects' respiratory outcomes and increase ventilator-free time tolerance. Methods Six patients (3 pediatric) underwent clinical DP implantation and started diaphragm conditioning, which involved progressively longer periods of daily, low intensity stimulation. Longitudinal respiratory breathing pattern, diaphragm electromyography, and pulmonary function tests were completed when possible, to assess feasibility of use, as well as diaphragm and ventilatory responses to conditioning. Results All subjects were eventually able to undergo full-time conditioning via DP and increase their maximal tolerated time off-ventilator, when compared to pre-implant function. Over time, 3 of 6 subjects also demonstrated increased or stable minute ventilation throughout the day, without positive-pressure ventilation assistance. Discussion Respiratory insufficiency is one of the main causes of death in patients with Pompe disease. Our results indicate that DP in Pompe disease was feasible, led to few adverse events and stabilized breathing for up to 7 years.